The role of the macrophage-to-myofibroblast transition in renal fibrosis - Wei, Jia; Xu, Zihao; Yan, Xiang (Frontiers in Immunology, 2022)
Renal fibrosis causes structural and functional impairment of the kidney, which is a dominant component of chronic kidney disease. Recently, a novel mechanism, macrophage-myofibroblast transition (MMT), has been identified as a crucial component in renal fibrosis responded for chronic inflammation. It is a process by which bone marrow-derived macrophages differentiates into myofibroblasts during the renal injury and promote renal fibrosis. Here, we summarized the recent evidence and mechanisms of MMT in renal fibrosis. Understanding this phenomenon and its underlying signal pathway would be beneficial to find therapeutic targets for renal fibrosis in chronic kidney disease.